Integrated effects of Kampo treatment on gastrointestinal symptoms and stress in patients with functional dyspepsia: a preliminary prospective observational study - Liang, Lian; Li, Hongyang; Doi, Hirokazu; Jiang, Yaxuan; Tashiro, Satoshi; Sun, Jiying; Kawahara, Akihiro; Oka, Shiro; Ito, Masanori; Ogawa-Ochiai, Keiko (Frontiers in Pharmacology, 2025)
AimThis preliminary, single-center prospective observational study aimed to investigate the effects of Kampo treatment on improving gastrointestinal symptoms and reducing stress levels in patients with Functional Dyspepsia (FD).MethodsAdult patients diagnosed with FD were included and their background characteristics were collected using a Fundamental State Questionnaire. The Gastrointestinal Symptom Rating Scale (GSRS) was used to assess gastrointestinal symptom improvement, and the Profile of Mood States Second Edition-Adult Short Form (POMS-2A) was used to evaluate stress relief both before and after treatment. Paired t-tests were used to compare the GSRS and POMS-2A scores before and after treatment. One-way ANOVA was applied to explore whether there were differences in efficacy among the three Kampo formulas, while Multiple linear regression was used to analyze the associations between patient characteristics and treatment outcomes.ResultsForty-one patients with FD were included, and thirty-three were included in the final analysis (N = 41, n = 33 analyzed). Following an average of 52 days of Kampo treatment (bukuryoin, heiisan, rikkunshito), there was a significant improvement in gastrointestinal symptoms, such as hunger, pain, constipation, and gastrectasia, as well as overall symptoms. Additionally, there was a significant decrease in negative mood components (anger and depression) and total mood disturbance. Marital status, smoking habits and sleep quality may serve as significant factors influencing the outcomes of Kampo treatment.ConclusionIn this exploratory and preliminary study, following Kampo treatment (bukuryoin, heiisan, rikkunshito), the trend of improvements in gastrointestinal symptoms and stress levels were observed in patients with FD. Additionally, marital status, smoking habits and sleep quality may serve as significant factors influencing treatment outcomes.